2011
DOI: 10.1007/s10549-011-1913-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative dose-dense sequential versus concomitant administration of epirubicin and paclitaxel in patients with node-positive breast cancer: 5-year results of the Hellenic Cooperative Oncology Group HE 10/00 phase III Trial

Abstract: To explore the impact of dose intensity (DI) in the adjuvant setting of breast cancer, a randomized phase III trial was conducted comparing postoperative dose-dense sequential chemotherapy with epirubicin, paclitaxel, and cyclophosphamide, methotrexate and fluorouracil (CMF)in high-risk breast cancer patients. From Oct 2000 to June 2005, 1,121 node-positive patients were randomized to dose-dense sequential epirubicin 110 mg/m(2) and paclitaxel (Taxol, Bristol Myers-Squibb, Princeton, NJ) 250 mg/m(2) (group A),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…The Hellenic Cooperative Oncology Group (HeCOG) conducted a randomized trial in Greece with node-positive breast cancer patients (n = 1,121) [26]. Patients were randomized to receive i) epirubicin every 14 days for 3 cycles followed by paclitaxel every 14 days for 3 cycles and then 3 more cycles of intensified CMF every 14 days or ii) paclitaxel and epirubicin every 21 days for 4 cycles followed by intensified CMF every 14 days.…”
Section: Trials Comparing More Than One Dose-dense Regimenmentioning
confidence: 99%
“…The Hellenic Cooperative Oncology Group (HeCOG) conducted a randomized trial in Greece with node-positive breast cancer patients (n = 1,121) [26]. Patients were randomized to receive i) epirubicin every 14 days for 3 cycles followed by paclitaxel every 14 days for 3 cycles and then 3 more cycles of intensified CMF every 14 days or ii) paclitaxel and epirubicin every 21 days for 4 cycles followed by intensified CMF every 14 days.…”
Section: Trials Comparing More Than One Dose-dense Regimenmentioning
confidence: 99%
“…The Hellenic Cooperative Oncology Group HE 10/00 phase II trial [8] investigated comparable regimens as adjuvant treatment for node-positive breast cancer. After a median follow-up of 5 years, the DFS (74% for both arms) and OS rates (86% for the dose-dense arm vs. 85% for the standard-dose arm) in patients receiving either dose-dense E(110)-P(250) q2w -CMF q2w or standard-dose E(83)-P(187) q3w -CMF q2w were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite comparable OS rates to our analysis after 5 years, the DFS rates of our analysis were worse with 63% and 55% in the dose-dense and standard-dose arm, respectively. The differences might be due to differences in the lymph node status [4,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of these trials are described in brief in S1 Table and detailed information about them can be found in the respective original papers [11][12][13]. At that time, trastuzumab was not licensed as adjuvant treatment; however it was administered in HER2 positive patients upon relapse [14].…”
Section: Patients and Methods Patientsmentioning
confidence: 99%